Representasi Nilai Moral dalam Cerita Rakyat Golan Mirah di Desa Nambang Rejo Kecamatan Sukorejo Kabupaten Ponorogo - Edy Suprayitno (JPK (Jurnal Pancasila dan Kewarganegaraan), 2018)
This study aimed at describing the realization of moral values within folklore of "Golan Mirah", originated from Nambang Rejo village, Sukorejo, Ponorogo. The moral value is reflected through plot and figures' character. Practically, the data were gathered through the following steps: (1) reading and re-reading the object carefully, and (2) taking the note any relevant findings. The result of study showed that "Golan Mirah" folklore contained moral values, as follows: (a) human and God relationship, (b) human and human relationship, and (c) relationship within individual. The relationships between human and God were realizad through (a) believe in God, (b) praying, and (c) doing shalah. The relationship among humans were realizad in giving advise, and friend to friend advise. The relationship within individual were realized through patience and sincerity.